How Do You Compare? - Jarocki, Zoe (Qualitative and Quantitative Methods in Libraries, 2019)
Assessment is a critical step instruction. Free response assessment questions provide unstructured insight into student’s understanding. However, it can be difficult to draw generalized conclusions from these sorts of responses. This presentation will share the methodology and results of a project in which we used content analysis to quantify and compare student responses to a post-library tour assessment. We created a taxonomy and applied the codes to the student responses in order to perform a content analysis. Once the answers were coded, we were able to compare the number of codes applied by each mode and what see what types of spaces, services and collections were mentioned. We concluded that the mobile tour was an acceptable replacement for the librarian lead tour.